The relationship of antihypertensive medication adherence and hypertension knowledge to quality of life in hypertensive patients - Wahyuni, Arlinda Sari; Eyanoer, Putri Chairani; Ritarwan, Kiking; Fujiati, Isti Ilmiati; Panjaitan, Alfred Johnatan; Sirait, Asima Rodiarta; Sekali, Oktaviani Karo; Elisabeth, Elisabeth; Ribawanto, Muhammad Rafif; Fachrezi, Muhammad Alfian; Faradila, Devita; Salsabila, Anisa; Risqin, Muhammad Anas Fatah; Nababan, Windika (Jurnal Prima Medika Sains, 2024)
Patient non-adherence to antihypertensive medication is a significant risk factor for increased morbidity and mortality in individuals with hypertension. Hypertension, a prevalent cardiovascular condition, is classified as a degenerative disease. Consistent antihypertensive treatment is crucial for improving patient quality of life. This study employed a cross-sectional survey design. The sample consisted of hypertensive patients who presented at the Belawan Health Center between July 22 and 26, 2024. Consecutive sampling was used to recruit 75 participants. Data were collected via interviews regarding participant characteristics and the administration of the Morisky Medication Adherence Scale-8 (MMAS-8), Hypertension Fact Questionnaire (HFQ), and World Health Organization Quality of Life-BREF (WHOQOL-BREF) questionnaires to assess medication adherence, hypertension knowledge, and quality of life, respectively. Analysis revealed strong positive correlations between medication adherence and quality of life (ρ = 0.677, p < .001), and between hypertension knowledge and quality of life (ρ = 0.700, p < .001). Furthermore, both medication adherence and hypertension knowledge significantly predicted quality of life (F = 53.704, p < .001). Multiple linear regression analysis (Y = 30.488) indicated that a one-unit increase in adherence was associated with a 2.680-unit increase in quality of life (p < .001), and a one-unit increase in knowledge was associated with a 2.704-unit increase in quality of life (p < .001). In conclusion, there are strong positive correlations between both medication adherence and hypertension knowledge with the quality of life of hypertensive patients at the Belawan Health Center.